Fruit fly fighters : eradication of the papaya fruit fly - Cantrell, B. K. (SCARM report, 2002)
The campaign to eradicate the papaya fruit fly from north Queensland has been widely acknowledged by international scientists as a significant technical achievement that equals any similar control program world-wide. Fruit Fly Fighters is a highly readable and practical account of the whole campaign from 1995 when the papaya fruit fly was first discovered until 1999 when eradication was formally declared. Key aspects covered include: The emergency response; Campaign management; The growers' perspective; Monitoring, eradication, data management; quarantine, traffic control points; market access for fruit from infected areas; public relations; and research and development.